2021
DOI: 10.37496/rbz5020200047
|View full text |Cite
|
Sign up to set email alerts
|

Practical procedures to body weight estimation and correction factors applied to Campolina horses

Abstract: The objective of this study was to evaluate the accuracy of the following six body weight (BW) estimation methods in Campolina (CAM) horses: A -weight tape placed at three different positions on the animal's thorax; B -Crevat and Quetelet's formula; C -Hall's formula; D -Hintz and Griffiths's table; E -Santos's table; and F -Cintra's formula. A total of 380 CAM horses were separated according to sex, age class, and gestational stage and evaluated. To determine their accuracy, weights measured on a scale and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Gender was also not recorded within the data set, so, again, this could not be investigated. In a study by Souza et al [ 26 ], it was found that a commercial weigh tape in Brazil was more accurate in male Campolina horses than in females. A previous study in 2017 using the same brand of weigh tape found that it overestimated female horses by an average of 7.4 kg and underestimated the weights of male horses by an average of 7.5 kg [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gender was also not recorded within the data set, so, again, this could not be investigated. In a study by Souza et al [ 26 ], it was found that a commercial weigh tape in Brazil was more accurate in male Campolina horses than in females. A previous study in 2017 using the same brand of weigh tape found that it overestimated female horses by an average of 7.4 kg and underestimated the weights of male horses by an average of 7.5 kg [ 27 ].…”
Section: Discussionmentioning
confidence: 99%